2006
DOI: 10.1002/chem.200500877
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Magnetic Properties of MnIII and CuII Tetranuclear Azido Polyoxometalate Complexes: Multifrequency High‐Field EPR Spectroscopy of Cu4 Clusters with S=1 and S=2 Ground States

Abstract: Two new azido-bridged polyoxometalate compounds were synthesized in acetonitrile/methanol media and their molecular structures have been determined by X-ray crystallography. The [[(gamma-SiW10O36)Mn2(OH)2(N3)(0.5)(H2O)(0.5)]2(mu-1,3-N3)](10-) (1 a) tetranuclear Mn(III) complex, in which an end-to-end N3- ligand acts as a linker between two [(gamma-SiW10O36)Mn2(OH)2]4- units, represents the first manganese-azido polyoxometalate. The magnetic properties have been studied considering the spin Hamiltonian H = -J1(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(28 citation statements)
references
References 65 publications
0
26
1
1
Order By: Relevance
“…[25] Figure6as hows the powder EPR spectrumo f1 (200 K), which at first view suggests almost axial symmetry.However,itisprobably aspectrum that encompasses many individually different Cu II centers, mutually accompanied by an et of strongm agnetic interactions. Figure 6b shows the single-crystal EPR spectrum of 1 with the crystal in an arbitrary orientation with respectt ot he magnetic field at 200 K. Possible hyperfine structurei sn ot resolved in either the powder or single-crystals pectrum,a lso as ar esult of strong magnetic interactions between the individually different Cu II centers.…”
Section: Powder and Single-crystal Epr Spectramentioning
confidence: 98%
“…[25] Figure6as hows the powder EPR spectrumo f1 (200 K), which at first view suggests almost axial symmetry.However,itisprobably aspectrum that encompasses many individually different Cu II centers, mutually accompanied by an et of strongm agnetic interactions. Figure 6b shows the single-crystal EPR spectrum of 1 with the crystal in an arbitrary orientation with respectt ot he magnetic field at 200 K. Possible hyperfine structurei sn ot resolved in either the powder or single-crystals pectrum,a lso as ar esult of strong magnetic interactions between the individually different Cu II centers.…”
Section: Powder and Single-crystal Epr Spectramentioning
confidence: 98%
“…[8] Recently, insertion into paramagnetic polyoxometalate matrices of exogenous ligands and especially that of the azido anion [9] has shown that such polydentate ligands can also allow the assembly of magnetic polyoxometalate subunits, [10] but in addition could impose ferromagnetic interactions within the cluster. [11,12] Co II polyoxometalate compounds containing from two to nine interacting paramagnetic centers have been reported.…”
Section: A C H T U N G T R E N N U N G [(A-a-siw 9 O 34 )A C H T U N mentioning
confidence: 99%
“…[8] This reaction mechanism has generally been accepted, although some detailed mechanistic work is still necessary. [4][5][6][7][8] Herein we report that the dicopper-substituted g-Keggin silicotungstate TBA 4 [g-H 2 SiW 10 O 36 Cu 2 (m-1,1-N 3 ) 2 ] (I, Figure 1; TBA = tetra-n-butylammonium) [9] is an effective homogeneous catalyst for the oxidative homocoupling of various kinds of structurally diverse alkynes [Eq. [4][5][6][7][8] Herein we report that the dicopper-substituted g-Keggin silicotungstate TBA 4 [g-H 2 SiW 10 O 36 Cu 2 (m-1,1-N 3 ) 2 ] (I, Figure 1; TBA = tetra-n-butylammonium) [9] is an effective homogeneous catalyst for the oxidative homocoupling of various kinds of structurally diverse alkynes [Eq.…”
mentioning
confidence: 99%
“…[10] The reaction proceeded efficiently even under 1 atm of air, although a longer reaction time was required (Table 1, entry 2). [9] respectively (Table 1, entries 3-5), [11] while non-polar 1,2dichloroethane and toluene were found to be poor solvents (Table 1, entries 6 and 7, respectively). Blue and green spheres show the copper and nitrogen atoms, respectively.…”
mentioning
confidence: 99%